Antibacterial and antioxidant activities of ethyl acetate extract of nettle (Urtica dioica) and dandelion (Taraxacum officinale) - Kais Kassim Ghaima, Noor Makie Hashim, Safaa Abdalrasool Ali (Journal of Applied Pharmaceutical Science, 2013)
The antibacterial and antioxidant activities of ethyl acetate extract of nettle (Urtica dioica) and dandelion (Taraxacum officinale) was studied, also phytochemical screening and determination of total phenolic content has been investigated. The results revealed that ethyl acetate extract of nettle was more effective on all bacterial isolates (Aeromonas hydrophila, Salmonella typhi, Staphylococcus aureus, Bacillus cereus, Escherichia coli) than dandelion with highest inhibition zone (24 mm) towards B. cereus, A hydrophila was more resistant than other bacteria. Also it was found that nettle gave large inhibition zone to S. typhi (22mm). Ethyl acetate of nettle had the highest content of phenolic compounds (48.3mg GAE/gdw) while dandelion had only (10.2 mg GAE/gdw) of phenolic content. The phytochemical qualitative screening exhibited flavonoid, glycosides and phenols were present in nettle and dandelion. In nettle, alkaloid, tannins and terpenoids were present, while absent in dandelion, on the other hand, dandelion had the saponins which not found in nettle. Steroids not present in the tow plants. Evaluation of antioxidant activities of ethyl acetate extract of nettle and dandelion by ferric thiocyanate method (FTC) exhibited that nettle caused 76% lipid peroxidation in inhibition of linoleic acid emulsion; this activity was greater than dandelion (44%) and α-tocopherol (65%).
Keywords: Nettle, dandelion, antibacterial, antioxidant and ph